Unsheltered Homeless Youth Point-in-Time Count and Outreach: Opportunities for University–Community Collaboration (Practice Note). Issue 3 (July 2016) - Trawver, Kathi R.; Aguiniga, Donna M.
Unaccompanied homeless youth (< 25 years of age) are the group most likely to be underreported in annual point-in-time (PIT) counts of unsheltered individuals. This practice note reviews the process of a collaborative partnership between a university and community to conduct a successful youth PIT count outreach that more accurately reflected the number of homeless youth. In addition to almost doubling the number of unsheltered homeless youth who were identified between 2013 and 2014, several positive outcomes for students, providers, and faculty resulted through the project's efforts. These outcomes, including increased student exposure and interest in this vulnerable population, are reviewed.